Ulcus Vulvae Acutum Lipschütz—UVAL: case series at a Swiss university hospital emergency room - Guareschi, Vittoria; Mathevet, Patrice; Jacot-Guillarmod, Martine (Frontiers in Reproductive Health, 2024)
Background: Ulcus Vulvae Acutum Lipschütz (UVAL) is a largely unknown disease with a broad and complex differential diagnosis.Objectives: to provide a description of the main characteristics of UVAL, determine the most appropriate diagnostic process and describe the current therapeutic approach.Methods: we designed a retrospective, descriptive cohort study using the gynecological-ER database of our institution. Inclusion criteria: female patients aged between 10 and 20 years old with suspicion of a UVAL diagnosis at CHUV's gynecological ER. Data extraction: epidemiological characteristics, clinical presentation, laboratory tests, established diagnostics, treatment, and ulcer outcomes.Results: 15 patients were included for the analysis; average age: 15 years old; 60% of patients were virgo at the time of ulcer onset; all patients had at least one flu-like symptom concomitant with the vulvar lesion; the most-performed serology was for EBV and acute disease was present in only one patient; for diagnostic purposes two biopsies were performed with both inconclusive histopathology analysis; the main prescribed treatments were: oral NSAIDs, Paracetamol, and Lidocaine gel; 93% of cases presented signs of regression; the average follow-up time was 10 days. The diagnostic algorithm of Sadoghi et al: 10 out of 15 cases were retrospectively diagnosed with UVAL by the algorithm; half were diagnosed with UVAL, and the other half received a diagnosis of "ulcers of unknown origin" at the time of the gynecological ER visit.Conclusions: we highly recommend the diagnostic and therapeutic algorithms developed by Sadoghi et al. as valuable tools to guide clinical reasoning and, consequently, improve acute vulvar ulcers management.